Proximate Determinant of Adolescents Fertility in Central Java (KEMAS: Jurnal Kesehatan Masyarakat, 2019)
Adolescent fertility is an important issue in terms of health and social care due to its relation to morbidity and mortality of mothers and children. The 2017 IDHS provided data regarding the percentage of women aged 15-19 who already became mothers or pregnant with their first child according to background characteristics. The 2017 IDHS results showed 7 percent of women aged 15-19 were mothers: 5 percent had given birth and 2 percent were pregnant with their first child. This study used a quantitative secondary data analysis approach. The secondary data used were the results of the Central Java IDHS 2017. The population of this study was all adolescent girls aged 15-19 years in Central Java. The unit analysis in the study were women of childbearing age which were 15-19 years from the analysis unit of Central Java IDHS in 2017 with a total sample of 4,560 respondents. From the results of the study, we noted that factors related to adolescent fertility in Central Java were age, education, use of contraception, marital status, status of living with a partner, and practice of sexual relations. Factors which were not related to adolescent fertility in Central Java were occupation, wealth, type of residential area, insurance ownership, duration of abstinence, partner's age, partner's level of education, and partner's occupation.